PENGARUH PERUBAHAN PREFERENSI GENERASI Z DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PADA WESTERN FOODS DI KOTA MATARAM, LOMBOK, INDONESIA - Dwi Nurdinda; Lalu Hamdani Husnan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine how changes in Generation Z preferences and product quality affect customer loyalty at Western Foods in Mataram City. Understanding the requirements and preferences of Generation Z is crucial for culinary businesses because this group is known to have dynamic and rapidly altered tastes. Furthermore, one of the elements that is thought to have a major role in fostering client loyalty is product quality. This study aims to provide actual data on how much these two factors affect the development of consumer loyalty. This study uses a survey approach in addition to a quantitative methodology. 200 Western Foods patrons in the Generation Z age group participated in the survey. Multiple linear regression analysis, validity and reliability testing, and traditional assumption tests were among the data analysis methods employed. The results of the study demonstrate that the Generation Z Preference variable has a positive and significant influence on customer loyalty, with significance and a t-value higher than the t-table below 0.05. The Product Quality variable has a positive and large impact on customer loyalty, and the coefficient supports this link. In all, this study demonstrates that product quality and Generation Z tastes are significant elements that can boost Mataram City customers' commitment to Western Foods. These findings imply that businesses need to pay attention to the dynamics of Generation Z preferences and maintain consistent product quality in order to retain customers in the long term.